(untitled) (Proceedings of International Educators Conference, 2024)
Bronchial asthma is one of the most common chronic respiratory diseases among children. This disease is characterized by inflammation and narrowing of the airways, which makes it difficult for children to breathe. Bronchial asthma in school-aged children can have a negative impact on their general health, learning and social functioning. Therefore, it is important to find effective ways to manage and treat asthma.